Assessment of Cervical Vertebrae Maturation Stages and the Accuracy of Age Estimation Methods in North Indian Population with Digital Lateral Cephalogram - Kohli, Ravshish Kaur; Arora, Manpreet; Puri, Pooja (Journal of the Indian Academy of Forensic Medicine, 2024)
Age estimation is mainly used for identification of unknown individuals in large-scale disasters, civil and criminal crimes, illegal immigration, child marriage, and juvenile cases. In many medico-legal cases, the age of an individual needs to be determined using population-specific reference criteria. Numerous techniques have been employed for estimating age, which involves morphological, histological, radiographical, and biological methods. The objective of the present study was to check the applicability of the cervical vertebrae maturation (CVM) method on the North Indian children population. A total of 500 lateral cephalograms (251 male subjects and 249 female subjects) were evaluated. The correlation between skeletal maturation age and chronological age of 6–16 years subjects was established by Spearman rank correlation. The Spearman’s rank correlation between age and skeletal maturation stages was estimated for both sexes (0.86 for males and 0.91 for females) and was statistically significant with P values ​​(<.001). The method has been accepted scientifically and effectively used on the North Indian children population in settling civil or criminal cases.